Natural autoimmunity in oligoarticular juvenile idiopathic arthritis - Elena Tsitsami; Ioannis Sarrigeorgiou; Maria Tsinti; Erasmia C. Rouka; Sotirios G. Zarogiannis; Peggy Lymberi (BMC, 2023)
Abstract Background Oligoarticular juvenile idiopathic arthritis (oligo-JIA) is considered as an antigen-driven lymphocyte-mediated autoimmune disease. Natural antibodies (NAbs) are pre-immune antibodies produced in the absence of exogenous antigen stimulation, participating in both, innate and adaptive immunity. Considering their major immunoregulatory role in homeostasis and autoimmune pathogenesis, we designed this study to further elucidate their role in oligo-JIA pathogenesis. Methods Seventy children with persistent oligo-JIA and 20 healthy matched controls were enrolled in the study. Serum IgM and IgA antibodies against human G-actin, human IgG F(ab΄)2 fragments and the hapten TriNitroPhenol (TNP) as well as the total concentration of serum IgM and IgA were measured by in-house enzyme-immunoassays. Kolmogorov-Smirnov normality test, Kruskal-Wallis H and Mann-Whitney tests were used to assess data distribution, and significant differences of non-parametric data between groups of the study. Backward regression analysis was used to analyze the effect of multiple factors (age, gender, disease activity, anti-nuclear antibody positivity, presence of uveitis) on continuous dependent variables (activities and activity/ concentration ratios of IgM and IgA NAbs). Results The ratios of IgA anti-TNP, anti-actin and anti-F(ab΄)2 levels to total serum IgA concentration were found to be significantly increased in patients with oligo-JIA compared to healthy subjects. Significantly elevated levels of IgM anti-TNP antibodies were also found in children with inactive oligo-JIA compared to those of children with active disease and of healthy controls. In the presence of anterior uveitis, IgM anti-TNP levels were significantly higher than in patients without uveitis or in healthy controls. Backward regression analysis revealed that the disease activity and the presence of anterior uveitis independently affect IgM anti-TNP levels. Conclusuions Our findings are in accordance with the hypothesis that NAbs contribute to the pathogenesis of autoimmune diseases and provide additional evidence that disturbances in natural autoimmunity may contribute to the as yet unclarified pathogenesis of oligo-JIA.